Community Participation Reviewed From Perceptions on Government Health Protocol Policy in Covid-19 Prevention - Sitti Chaeriah Ahsan; Slamet Riadi; Donal Adrian (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The corona-19 virus is a new disease that emerged in 2019 and is very dangerous for the health of the human body. To prevent the spread of the corona-19 virus in Indonesia, including in Central Sulawesi, the government implemented a health protocol policy. This study aims to determine the public's perception of health protocol policies by the government. The research uses qualitative methods. The informants consisted of the people of Nupabomba Village as a trans-Sulawesi route. Data collection techniques using observation and in-depth interviews. Data analysis consists of data reduction, data display, and conclusion drawing. The results of the study show that the public can provide positive perceptions related to policies regarding the prevention of the corona virus-19. This perception is marked by a responsibility to comply with health rules and be able to explain well to fellow people related to the dangers of covid-19 so that habit patterns must be changed by using masks, washing hands in running water, maintaining distance, reducing mobility, and staying away from crowds.